Antipyretic Therapy in Critically Ill Septic Patients: A Systematic Review and Meta-Analysis. Issue 5 (May 2017) - Drewry, Anne M.; Ablordeppey, Enyo A.; Murray, Ellen T.; Stoll, Carolyn R. T.; Izadi, Sonya R.; Dalton, Catherine M.; Hardi, Angela C.; Fowler, Susan A.; Fuller, Brian M.; Colditz, Graham A.
Abstract : Objective: This meta-analysis aimed to examine the impact of antipyretic therapy on mortality in critically ill septic adults. Data Sources: Literature searches were implemented in Ovid Medline, Embase, Scopus, Cumulative Index of Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials, NHS Economic Evaluation Database, andClinicalTrials.gov through February 2016. Study Selection: Inclusion criteria were observational or randomized studies of septic patients, evaluation of antipyretic treatment, mortality reported, and English-language version available. Studies were excluded if they enrolled pediatric patients, patients with neurologic injury, or healthy volunteers. Criteria were applied by two independent reviewers. Data Extraction: Two reviewers independently extracted data and evaluated methodologic quality. Outcomes included mortality, frequency of shock reversal, acquisition of nosocomial infections, and changes in body temperature, heart rate, and minute ventilation. Randomized and observational studies were analyzed separately. Data Synthesis: Eight randomized studies (1, 507 patients) and eight observational studies (17, 432 patients) were analyzed. Antipyretic therapy did not reduce 28-day/hospital mortality in the randomized studies (relative risk, 0.93; 95% CI, 0.77–1.13; I 2 = 0.0%) or observational studies (odds ratio, 0.90; 95% CI, 0.54–1.51; I 2 = 76.1%). Shock reversal (relative risk, 1.13; 95% CI, 0.68–1.90; I 2 = 51.6%) and acquisition of nosocomial infections (relative risk, 1.13; 95% CI, 0.61–2.09; I 2 = 61.0%) were also unchanged. Antipyretic therapy decreased body temperature (mean difference, –0.38°C; 95% CI, –0.63 to –0.13; I 2 = 84.0%), but not heart rate or minute ventilation. Conclusions: Antipyretic treatment does not significantly improve 28-day/hospital mortality in adult patients with sepsis. Abstract : Supplemental Digital Content is available in the text.